Gold Coated Superparamagnetic Iron Oxide Nanoparticles as Effective Nanoparticles to Eradicate Breast Cancer Cells via Photothermal Therapy - Ehsan Nassireslami; Morteza Ajdarzade (Tabriz University of Medical Sciences, 2018)
Purpose: Unique physiochemical properties of Fe2O3 nanoparticles make them great agents to serve as therapeutic and diagnostic nanoparticles (NPs). In this study, we developed gold coated Fe2O3 nanoparticles for photothermal therapy of breast cancer cells. Methods: Fe2O3 nanoparticles was prepared via microemulsion method and their surface was modified via gold. Differential light scattering (DLS) and transmission electron microscopy (TEM) methods were applied to evaluate physicochemical properties of NPs. Gold coated NP was further modified with MUC-1 aptamer as a targeting agent to increase drug delivery into the desired tissue. To evaluate cytotoxicity of prepared cells, MTT assay was employed. Targeting ability of aptamer modified NPs was assessed through confocal microscopy and flow cytometry method. Subsequently, MCF-7 and CHO cells were treated with aptamer modified NPs and were then irradiated via near infrared light (NIR) to produce heat. Results: The morphology of NPs was spherical and monodisperse with the size of 16 nm, which was confirmed via DLS and TEM. Confocal microscopy and flow cytometry results indicated that aptamer modified NPs had higher uptake compared to bare NPs. Finally, NIR exposure results revealed that higher uptake of NPs and application of NIR led to significant death of MCF-7 cells compared to CHO cells. Conclusion: To sum up, aptamer modified Fe2O3 nanoparticles showed higher uptake by cancerous cells and led to eradication of cancerous cells after exposure to NIR light.